The Relationship between Demographic Characteristics, Job Stress, Work Culture and Work-Life Balance with Job Satisfaction - Yunus, Noor’ain Mohamad; Charlie, Asallina Daya Anak; Ali, Syukrina Alini Mat; Jailani, Sri Fatiany Abdul Kader (Advances in Social Sciences Research Journal, 2023)
Job satisfaction is a topic of great interest and a critical factor that affects organizational success. Job satisfaction is a complex phenomenon which is determined by multiple variables. Therefore, there is a need to investigate the factors influencing job satisfaction for the benefit of both employees and employers. Guided by Frederick Herzberg Two Factor Theory (1959), this correlational study attempted to examine the relationship between demographic characteristics, job stress, work culture and work-life balance with job satisfaction among the employees in one Port in Malaysia. Questionnaires were used as the main instrument. A total of 150 questionnaires were distributed online to the employees through a convenience sampling technique. The findings revealed a significant relationship between gender, work culture, job satisfaction, and work-life balance with job satisfaction among employees. Understanding factors related to job satisfaction is crucial for improving organizational performance and helping employees lead more fulfilling and satisfying professional lives.